A new computational approach for three-dimensional singular stress analysis of interface voids - Zhang, Yuxuan (2021)
Defects in terms of three-dimensional voids are commonly encountered at bi-material interfaces. In the current study, the singular stress field near the circumferential corner line of a three-dimensional axisymmetric interfacial void is analyzed using our newly established singular interface edge elements. Under the premise that ρ≪ R, the proposed singular element method does not depend on the size of the element; thereby, it is not necessary to use refined elements at the interface corner line. The numerical results reveal the intensity of the stress singularity at the interface line of the three-dimensional axisymmetric voids. The obtained stress intensity parameters can be used to judge the local fatigue crack initiation. The geometry effect of the void on the singular stress field at the circumferential interface corner line is studied and discussed in detail.